From Religious Tolerance to «Libertà del Pensare». The Thought of the Jansenist Abbot Pietro Tamburini (1737-1827), Professor at the University of Pavia (Italian Review of Legal History, 2017)
The paper seeks to outline the thought on the theme of tolerance by the Jansenist Abbot Pietro Tamburini, Natural Law Professor at the legal faculty of the University of Pavia. From the study of his works, it emerges a bifocal jurisdictionalist and natural-law reading.In this dual perspective, it’s analyzed the concept of ecclesiastical and civil tolerance in religious matters, with particular attention to the issue of sovereignty and the right to punish and then bring the issue to the relationship between personal property, freedom of thought and exercise of intellectual faculties.
Keywords: tolerance; jurisdictionalism; natural law; personal property; freedom of thought